KEMUNGKINAN MALARIA PRIMATA SEBAGAI MASALAH ZOONOSIS - Shinta, Shinta (Badan Penelitian dan Pengembangan Kesehatan, 2001)
Until today, four species of Plasmodium are pedicular to inan Plasmodium falciparum, P. vivax, P. malariae, and P. ovale) and at least five species are common in simian: Plasmodium inue, P. cynomolgy, P. knowlesi, P. brasilianum and P. simium. There is little doubts that simian Plasmodium can infect man, it is known as zoonosis. Number of cases of zoonosis infection of simian Plasmodium have been reported from several countries; P. knowlesi (1965), in America, P. simium (1966) in Brazilia, P. inui (1971) in Pahang Malaysia, P. cynomolgi (1973) in America and P. Brazilianum in Sao Paulo (1966, 1995). While pro and contra about zoonotic malaria still not clearly discussed, the new cases have occurred. This give an indication that this zoor >tic malaria will probably be in Indonesia where human, primate, Plasmodium (agents) and vector live in the same ecosystem. This paper will discuss the simian Plasmodium and its possibility to be a zoonotic malaria.",